Research on inhibiting properties of new schale deposition reagents - Aga-Zade A. D.; Cavadova L. A.; Kholmurodova Dilafruz; Ungalov Sanjar (BIO Web of Conferences)
New compositions for inhibiting scale deposits on oil-field equipment and pipelines have been developed based on a nitrogen- containing compound, inhibited hydrochloric acid, anionic polymer and water. The efficiency of inhibiting scale deposits was assessed using artificially prepared mineral waters of carbonate and sulfate types, simulating formation waters. It was found that the introduction of the prepared compositions into calcium sulfate and calcium carbonate solutions at a rate of 50 mg/l provides a high protective effect compared to an inhibitor consumption of 30 mg/l. The content of the active substance in the compositions is 14.5 – 18.5%.